RESEARCH OF PHYSICAL AND MECHANICAL PROPERTIES OF BLENDED BRICKS WİTH FLY ASH BASED, BLAST FURNACE SLAG ADDITION - Çağlar, Hakan; Çağlar, Arzu (Granthaalayah Publications and Printers, 2019)
In this study, it is aimed to make improvements on blended brick (1) which is the first building material has a history of at least 10,000 years. To the blended brick which is a traditional material was kept constant at 5% the addition of fly ash which is industrial waste. It was aim of determine of the effect on the physical and mechanical properties of the blended brick using different ratios (5%, 10%, 15% and 20%) blast furnace slag. In the first stage, the production of fly ash-based blast furnace slag doped sample of blended brick was performed. In the second stage, a variety of experiments were applied to determine the physical and mechanical properties of the blended brick sample. As a result; It has been determined that unit volume weight and compressive strength decreases with the use of industrial wastes in blended brick production. They have occured an increase in porosity and capillary water absorption values. The use of industrial wastes in the production of blended bricks will contribute both improve the properties of the bricks and   the reduction of wastes left to the environment.
Keywords: Flay Ash; Blast Furnace Slag; Brick; Physical Property; Mechanical Property.; 12. Responsible consumption